Ultrasound Based Flow Measurements of the Left and Right Carotid System of Arteries in Bangladeshi Patients (Bangladesh Heart Journal, 2023)
Carotid arteries are the major supply to the head, neck and brain.  The right common carotid artery usually originates from the brachiocephalic artery while the left common carotid artery arises as a direct branch of the arch of the aorta. Common carotid arteries bifurcate at the level of the carotid sinus into the internal carotid artery, which supplies the brain, and the external carotid artery. Approximately 15–20% of the cardiac output is distributed to the brain in healthy adults under resting conditions. Cardiovascular diseases are the leading cause of death globally, taking an estimated 17.9 million lives each year. US 2017 statistics shows that cerebrovascular disease or Stroke alone ranked fifth for males but fourth for females. Ultrasonography can measure the velocity of blood flow in the Carotid system of arteries. A total 139 patients, who underwent Carotid Duplex study between July 2021 and June 2022 were included in this cross-sectional study. The criteria for exclusion included age less than 13 years, presence of associated peripheral vascular diseases, hemodynamically unstable patients, incomplete data collection and patient’s reluctance to join the study. Data analysis was performed using MS Office Excel. The Peak systolic velocity and the End diastolic velocity were measured at four levels, namely the Common carotid arteries and the Internal carotid arteries on the right and the left sides. No significant difference was observed in the Peak systolic velocity and the End diastolic velocity in either Common carotid or the internal carotid arteries between the right and left sides. Moreover, these findings were similar both in age groups above and below 50 years of age.Bangladesh Heart Journal 2023; 38(2): 110-114